Innovations in rural and agricultural finance: New approaches for index insurance: ENSO insurance in Peru - Skees, Jerry; Collier, Benjamin (International Food Policy Research Institute, 2010)
The El Niño Southern Oscillation (ENSO) is a climate event associated with warming sea surface temperatures in the Pacific Ocean. In years of extreme El Niño events, areas in northern Peru experience catastrophic flooding. As of 2010, it is possible for stakeholders in northern Peru to purchase a new form of insurance that pays out just as flooding begins and stakeholders begin incurring extra costs and consequential losses.